Designing circuit boards with Eagle : make high-quality PCBs at low cost - Scarpino, Matthew (Upper Saddle River, New Jersey : Prentice-Hall, 2014)
Part I. Preliminary introduction -- Introducing EAGLE -- An overview of circuit boards and EAGLE design -- Designing a simple circuit -- Part II. Designing the Arduino Femtoduino -- Designing the Femtoduino schematic -- Layout and design rules -- Routing -- Generating and submitting output files -- Part III. Advanced capabilities -- Creating libraries and components -- Simulating circuits with LTspice -- Part IV. Automating EAGLE -- Editor commands -- Introduction to the user language (UL) -- Examining designs with the user language -- Creating dialogs and menu items -- Part V. The BeagleBone Black -- Schematic design for the BeagleBone Black -- Board design for the BeagleBone Black.
Includes index.
Keywords: PRINTED CIRCUITS